Analysis of the Policy Discourse of the Regional Revenue Agency (Bapenda) in Determining the Valuation of Land Sales and Purchases in Palopo City - Citra Nur Safitri; Arafat Yusmad, Muammar; Takdir (Institut Agama Islam Negeri Palopo, 2024)
This research examines the policy discourse analysis of the Regional Revenue Agency (Bapenda) in determining the valuation of land sales and purchases in Palopo City. The main focus of the research is to analyze how the policy discourse is constructed, implemented, and its impact on the process of determining the value of land buying and selling transactions. Using a critical discourse analysis approach and qualitative research methods, this research collected data through in-depth interviews with Bapenda officials, notaries and the public, as well as analysis of related policy documents. The research results show that the land assessment policy discourse in Palopo City is influenced by various factors, including the interest in increasing local revenue, property market dynamics, and community socio-economic considerations. This research also reveals the gap between formal policies and implementation in the field, as well as identifying challenges in achieving a balance between optimizing regional income and justice for the community. These findings provide an important contribution to the development of more effective and fair regional revenue management policies.